Kinematic analysis on the forehand stroke of ATP tennis player Karen Khachanov - Du, C. J.; Zhou, J. H.; Wang, S. (MATEC Web of Conferences, 2017)
By using the three-dimensional video analysis method to kinematic analyze the forehand stroke technique of the ATP professional tennis player, Karen Khachanov. Exploring the action mode and characteristics from him to provide a reference for all tennis learners to improve their forehand stroke. The results show that: (1) At the end of the preparation, Karen Khachanov`s center of gravity was lower, and his body control was steady; (2) After the follow through, each joint of Karen Khachanov`s racquet arm were stretched, so the swing radius is larger. His right leg was like a support point for the next stage---drive leg and rotate hip; (3) At the swing stage, the move of his driving leg and rotating hip was full, so the whole hitting action match the principle whipping technique movement. (4) The "wiper " style follow through was natural, coordinated, and smooth. After hitting the ball, his body of control was steady, the shoulder movement was obvious, and the hitting was fast and powerful. Conclusion: The forehand stroke of Karen Khachanov was a high quality hitting action, and it`s worthy of tennis players to learn from.